Analysis of organoleptic properties and consumer acceptance of frozen noodle products - Zuhdi, Muhson; Khairi, Amalya Nurul (Journal of Halal Science and Research, 2022)
Frozen noodles are a type of noodles that undergo a boiling process after the noodle printing stage so that the moisture content reaches 52%. An organoleptic test is a sensory test with testing using human senses as the primary tool in measuring acceptance power. The purpose of writing this journal is to determine organoleptic properties and consumer acceptance of frozen noodle products. The method used was a hedonic test on 20 semi-trained panelists. The parameters tested were color, aroma, suppleness, softness, stickiness, taste, and degree of liking. The parameters that consumers most like are in terms of the color of the noodles, while the parameters that consumers do not like are the stickiness of the noodles.